Resistance that Cannot Be Recognized as Such: Interview with Gayatri Chakravorty Spivak - Suzana Milevska; Gayatri Chakravorty Spivak; Mirushe Hodja (Identities, 2003)
Author(s): Suzana Milevska and Gayatri Chakravorty Spivak | Сузана Милевска и Гајатри Чакраворти Спивак